PSIKOLOGI BELAJAR BAHASA ARAB - Hani'atul Khoiroh (Universitas Kiai Abdullah Faqih Gresik, 2018)
Abstract: Psychology is a science about soul that studies attitudes and behavior as expressions of the state of the soul that exists. While learning psychology implies the science of human behavior in learning activities. In conjunction with Arabic material means the science that tries to trace, study, discuss, and observe the behavior of individuals in the process of getting a variety of Arabic language abilities, in which it also contains an understanding of how one learns Arabic. So, this knowledge devotes its attention to behavior or actions or behavior of people who carry out Arabic learning activities which includes four language skills whether listening, speaking, reading or writing. The purpose of this article is to explore the problems of learning by looking in terms of psychology, namely a review of psychology with a Psychology approach to Learning Arabic. Key Word: Psikologi, Belajar, Bahasa Arab